Diseño de envases y embalajes para productos alimenticios y textiles de la comunidad Palacio Real - Marcillo Benavides, Diana Marcela (2018)
The research was carried out in the Cultural Museum of the Llama that is located in the community of Palacio Real, province of Chimborazo. There, textile and food products derived from the flame are produced. There are previous studies and investigations related to community tourism, without taking into account that one of the main products is textiles. These products demand the creation of packaging, which in turn are elements of a positioning strategy within the sector. The need was identified by implementing different design stages following Scott's design methodology. The proposals for packaging proposals were elaborated, based on laws and principles of design (Gestalt, Principles of good design). The proposal evidences the use of modular systems for the development of the prototypes, guaranteeing the fulfillment of the basic, stacking and communicational functions of the packaging; also respecting the regulations in force. We experimented with materials and technologies suitable for the construction of prototypes as final pieces. A methodological process and theoretical foundation was carried out that guarantees the scientific rigor that sustains the typologies of design, to obtain aesthetic, ecological and functional pieces. its application will influence the positioning of the products in a strategic way within the market, thanks to the design process fulfilled.